'Stayhome' as a YouTube performance: representing and reshaping domestic space under the 2020 covid lockdown in Italy. Issue 2 (15th March 2022) - Boccagni, Paolo; Brodesco, Alberto; Bruna, Federico La
ABSTRACT: What does 'staying at home' mean, and how is it represented online, once it suddenly becomes a legal obligation? This article explores the ways to display and resignify the domestic space through the frames of YouTube during the first nationwide lockdown in Italy in spring 2020. While being enforced at home, and possibly as a way to cope with this, YouTube creators perceive, display and (re)adapt their dwellings in contrasting ways along the continuum between safe shelter and prison; as proper domestic space but also as functional equivalent of extra-domestic ones such as gyms and offices; as the necessary backdrop for their performances or as a setting to be exhibited in its own right. Based on a content analysis of 989 videos using the hashtag #iorestoacasa ['I'm staying home'] between March and May 2020, this article explores how the domestic space is turned into a stage for public (YouTube-mediated) activities, thereby revealing an increasing permeability between private and public domain. This, in turn, invites to further investigate the complex entanglements of private and public, 'displayed' and 'invisibilized', as an expression of the constitutive ambivalence of the home.